Designing Multifunctional Cobalt Oxide Layers for Efficient and Stable Electrochemical Oxygen Evolution. Issue 21 (24th June 2022) - Kuhl, Matthias; Henning, Alex; Haller, Lukas; Wagner, Laura I.; Jiang, Chang‐Ming; Streibel, Verena; Sharp, Ian D.; Eichhorn, Johanna
Abstract: Disordered and porous metal oxides are promising earth‐abundant and cost‐effective alternatives to noble‐metal electrocatalysts. Herein, nonsaturated oxidation in plasma‐enhanced atomic layer deposition is leveraged to tune the structural, mechanical, and optical properties of biphasic cobalt hydroxide films, thereby tailoring their catalytic activities and chemical stabilities. Short oxygen plasma exposure times and low plasma powers incompletely oxidize the cobaltocene precursor to Co(OH)2 and result in carbon impurity incorporation. These Co(OH)2 films are highly porous and catalytically active, but their electrochemical stability is impacted by poor substrate adhesion. In contrast, long exposure times and high powers completely oxidize the precursor to Co3 O4, reduce the carbon incorporation, and improve the crystallinity. While the Co3 O4 films have high electrochemical stability, they are characterized by low oxygen evolution reaction activity. To overcome these competing properties, the established relation between deposition parameters and functional film properties is applied to design bilayer films exhibiting simultaneously improved electrochemical performance and chemical stability. The bilayer films combine a highly active Co(OH)2 surface with a stable Co3 O4 interface layer. These coatings exhibit minimal light absorption, thus making them suitable as protective catalytic layers on semiconductor light absorbers for application in photoelectrochemical devices. Abstract : Disordered and porous metal oxides are promising earth‐abundant and cost‐effective alternatives to noble‐metal electrocatalysts. Herein, nonsaturated oxidation in plasma‐enhanced atomic layer deposition is leveraged to tune the structural, mechanical, and optical properties of biphasic cobalt oxide films, thereby tailoring their catalytic activities and chemical stabilities.